2022
DOI: 10.1038/s41598-022-07862-5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of barbed continuous suture versus conventional interrupted suture for fascial closure in total hip arthroplasty

Abstract: A barbed suture is a self-anchoring knotless suture hypothesized to shorten suture time and reduce the tension point of the wound. The purpose of this study was to compare the barbed suture and the interrupted suture for fascial closure in total hip arthroplasty. We retrospectively reviewed patients who underwent total hip arthroplasty from March 2014 to June 2020. We evaluated 324 cases among 274 patients consisting of 188 males and 86 females. We collected the following data: demographics, time for wound clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…As previously reported and in the study described, closure of the incision took less time using the barbed suture than the standard suture 1,4–6,41–43 . Multiple studies support the assumption that an extended duration of surgery and anesthesia are associated with higher surgical site infection rates 28,31,44 .…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…As previously reported and in the study described, closure of the incision took less time using the barbed suture than the standard suture 1,4–6,41–43 . Multiple studies support the assumption that an extended duration of surgery and anesthesia are associated with higher surgical site infection rates 28,31,44 .…”
Section: Discussionsupporting
confidence: 55%
“…As previously reported and in the study described, closure of the incision took less time using the barbed suture than the standard suture. 1,[4][5][6][41][42][43] Multiple studies support the assumption that an extended duration of surgery and anesthesia are associated with higher surgical site infection rates. 28,31,44 In human arthroplasty the reduced wound closure time obtained when using barbed sutures has been reported to reduce overall costs by saving operative time.…”
Section: Barbedmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, a study by Sunhyung Lee et al . 7 from South Korea reported that barbed sutures have demonstrated a consistent trend of reducing operation time and maintaining a comparable rate of wound complications in the field of orthopedic surgery. In contrast, Junho Mun et al .…”
Section: Introductionmentioning
confidence: 98%